Phospholamban Modulates the Functional Coupling between Nucleotide Domains in Ca-ATPase Oligomeric Complexes in Cardiac Sarcoplasmic Reticulum - Chen, Linda T.L. (2009)
Oligomeric interactions between Ca-ATPase polypeptide chains and their modulation by phospholamban (PLB) were measured in native cardiac sarcoplasmic reticulum (SR) microsomes. Progressive modification of Lys(514) with fluorescein-5-isothiocyanate (FITC), which physically blocks access to the nucleotide binding site by ATP, demonstrates that Ca-ATPase active sites function independently of one another prior to the phosphorylation of PLB. However, upon PKA-dependent phosphorylation of PLB, a second-order dependence between residual enzyme activity and the fraction of active sites is observed, consistent with a dimeric functional complex. Complementary distance measurements were made using FITC or 5-iodoacetamido-fluorescein (IAF) bound to Cys(674) within the N- or P-domains respectively, to detect structural coupling within oligomeric complexes. Accompanying the phosphorylation of PLB, neighboring Ca-ATPase polypeptide chains exhibit a 4 ± 2 Å decrease in the proximity between FITC sites within the N-domain and a 9 ± 3 Å increase in the proximity between IAF sites within P-domains. Thus, the phosphorylation of PLB induces spatial rearrangements between the N- and P-domain elements of proximal Ca-ATPase polypeptide chains which restore functional interactions between neighboring polypeptide chains and, in turn, result in increased rates of catalytic turnover. These results are interpreted in terms of a structural model, calculated through optimization of shape complementarity, desolvation, and electrostatic energies, which suggests a dimeric arrangement of Ca-ATPase polypeptide chains through the proximal association of N-domains that accommodates interaction with PLB. We suggest that the phosphorylation of PLB acts to release constraints involving interdomain subunit interactions that enhance catalytically important N-domain motions.